Rapid changes in gene expression: DNA determinants of promoter regulation by the concentration of the transcription initiating NTP in Bacillus subtilis - Sojka, Ludek; Kouba, Tomás; Barvík, Ivan; Sanderová, Hana; Maderová, Zdenka; Jonák, Jirí; Krásny, Libor (Nucleic acids research, 2011)
In bacteria, rapid changes in gene expression can be achieved by affecting the activity of RNA polymerase with small molecule effectors during transcription initiation. An important small molecule effector is the initiating nucleoside triphosphate (iNTP). At some promoters, an increasing iNTP concentration stimulates promoter activity, while a decreasing concentration has the opposite effect. Ribosomal RNA (rRNA) promoters from Gram-positive Bacillus subtilis are regulated by the concentration of their iNTP. Yet, the sequences of these promoters do not emulate the sequence characteristics of [iNTP]-regulated rRNA promoters of Gram-negative Escherichia coli. Here, we identified the 3'-promoter region, corresponding to the transcription bubble, as key for B. subtilis rRNA promoter regulation via the concentration of the iNTP. Within this region, the conserved -5T (3 bp downstream from the -10 hexamer) is required for this regulation. Moreover, we identified a second class of [iNTP]-regulated promoters in B. subtilis where the sequence determinants are not limited to the transcription bubble region. Overall, it seems that various sequence combinations can result in promoter regulation by [iNTP] in B. subtilis. Finally, this study demonstrates how the same type of regulation can be achieved with strikingly different promoter sequences in phylogenetically distant species.
Keywords: DNA-Directed RNA Polymerases; Bacillus subtilis; DNA, Bacterial; Escherichia coli; DNA bakterií; Genes, rRNA; Kinetics; Nucleotides; genetická transkripce; promotorové oblasti (genetika); geny rRNA; Promoter Regions, Genetic; nukleotidy; Transcription, Genetic; kinetika; Gene Expression Regulation, Bacterial; DNA řízené RNA-polymerasy; regulace genové exprese u bakterií